Functional outcome of hybrid external fixator in proximal tibial fractures Schatzker type V and VI with Gustillo grade-II - Juneja, Johney; Asiger, Mohzin; Kumar, Dinesh; Joshi, Vinay; Jain, Mahendra P.; Garg, Gaurav; Mehra, A. K. (International Journal of Research in Orthopaedics, 2021)
Background: Management of high energy tibial plateau fractures along with extensive soft tissue damage is still challenging to many orthopaedic surgeons. This study evaluates the purpose of hybrid external fixator intreating high energy tibial plateau fractures with minimal invasion and accurate reduction. Methods: Twenty patients with high energy Schatzker type V and VI tibial plateau fractures with severe soft tissue injury were enrolled into the study in RNT medical college, Udaipur. Results: The results- bony union, range of movements and associated complications were assessed. All fractures united in an average time period of 20 weeks. Ten patients developed knee stiffness, five patients developed delayed union andthreenon-union.15 patients required split skin graft. Final outcome showed excellent score in 53 patients. Conclusions: Hybrid external fixation is a safe option for managing complex high energy tibial plateau fractures by simultaneously providing adequate fracture stabilization and necessary protection to soft tissue healing to achieve bony union.